Peningkatan Pengetahuan Kader Tentang Kesehatan dan Kebugaran pada Lansia di Posyandu Lansia Melati, Bendosari, Sukoharjo - Tsania Haifa’ Kurniahadi; Fahra Fadhilla; Aldin Nasrun Minalloh; Muhammad Isa Hanafi; Siti Azzura Zain; Dwi Rosella Komalasari (STIKes Ibnu Sina Ajibarang, 2024)
Health and fitness for the elderly is important in maintaining their quality of life and independence. This community service activity aimed to increase cadres' knowledge about health and fitness for the elderly at Posyandu Lansia. Posyandu cadres are important in providing information and health services for the elderly. Through structured training and education, it is hoped that cadres better understand and implement optimal health practices for the elderly. The methods used counselling sessions, material discussions, assisting cadres in providing physical exercise to improve physical fitness, assisting cadres in carrying out elderly fitness checks using the six-minute walking test (6MWT), as well as pre-post tests to determine the success of cadres' understanding, about the material that has been given. The activity results showed a significant increase in cadres' knowledge regarding the fitness and health aspects of the elderly, with the average score on the pre-test being 65,625 to 90 on the post-test. In addition, cadres reported increased confidence in providing physical exercise education to the elderly and measuring physical fitness with the 6MWT. In conclusion, this training program effectively increases the knowledge and capacity of cadres, which can contribute to improving the quality of life of elderly people in elderly communities. This service activity recommends implementing similar programs in other posyandu to improve the fitness and health of the elderly at large.